Influence of current density on the characteristics of diamond grains-nickel super-thin cutting blade fabricated by electrotyping. (15th October 2007) - Fang, L.L.; Zhang, B.L.; Deng, J.C.; Yao, N.
Free-standing diamond grains-nickel composite films were deposited by using electrotyping method at the condition of low internal stress electrolytic solution. The effect of electric current density on the diamond grain concentration, surface morphology, microstrain (or lattice strain) and deposition rate of the film was studied. Scanning Electron Microscope (SEM) and X-Ray Diffraction (XRD) were used to analyse the characteristics of the films. It was found that the diamond grain concentration in the film varied with current density and approached to its maximum value when the current density was at the range of 1.3?2.5 A/dm?. The microstrain in the film decreased from 0.36 to 0.28% with increase of the current density from 1.3 to 3.3 A/dm?. The deposition rate of the film increased with an increase of current density. The film with the best possible density and uniformity was obtained at the current density range of 1.3?2.0 A/dm?. The composite films obtained in this study can be used to make super-thin cutting blade for cutting Integrated Circuit (IC) silicon chips as well as other electronic devices.